Public Audit and Its Role in Enhancing Industrial Policy Innovation in Ghana - Afadzinu , Sewornu Kobla; Németh, Erzsébet; András, Szeberényi (Journal of Ecohumanism, 2024)
Objective: This study explores the role of public audits in enhancing industrial policy innovation in Ghana. Theoretical Framework: The research is grounded in agency theory to understand the principal-agent relationship between auditors and policymakers, highlighting the need for audits to go beyond mere compliance to foster dynamic governance. Additionally, innovation systems theory, is utilized to grasp the systemic interactions among various actors (government, industry, academia, and civil society) in driving innovation. Method: A qualitative research approach was employed for the study, utilizing documentary analysis as the method for data collection and analysis. Results and Discussion: The results revealed that the current focus of GAS on financial compliance limits the potential of audits to drive innovation in industrial policy. Weak feedback mechanisms and insufficient collaboration between GAS and industrial stakeholders further inhibit the influence of audit recommendations on policy changes. Research Implications: The study underscores the need for a reorientation of the GAS’s approach to public auditing, advocating for a broader scope that includes innovation-focused evaluations. This shift could lead to more meaningful policy reforms and improved economic outcomes in Ghana. Originality/Value: This research contributes to the existing literature by highlighting the untapped potential of public audits as catalysts for innovation within Ghana’s industrial policy framework. It provides actionable recommendations for policymakers and audit institutions, emphasizing the importance of integrating innovation metrics into public auditing practices to foster sustainable economic growth